Gratitude Cognitive Behavior Therapy (G-CBT) to Reduce College Students’ Academic Stress - Muhana Sofiati Utami; Mar'atush Shalihah; Nanda Putri Adhiningtyas; Siti Rahmah; Winda Kartika Ningrum (Jurnal Psikologi, 2020)
Stress cannot be separated from student academic life in university. This stressful condition, if not managed properly, can prevent students from successfully completing their studies. This study aimed to examine the effects of Gratitude-Cognitive Behavior Therapy (G-CBT) in reducing academic stress among students. Sixteen students were recruited for this research, all of which were working on their thesis projects. Among these participants, 10 were assigned to the experimental group and six were assigned to the control group. The effect of the intervention was tested using a quasi-experiment with an untreated control group design with pretest and posttest samples. The Academic Stress Scale and the Grateful Scale were used to measure academic stress and gratitude. Analysis using the non-parametric Mann-Whitney U Test showed that following the administration of G-CBT treatment, there was a larger reduction of academic stress among participants in the experimental group compared to the control group (Z = -3.264; p <0.05). The study concluded that G-CBT intervention can reduce academic stress on students.